Tolerance in Pakistani Urdu Short Story: A Study of Ishfaq Ahmad - Arshad, Muhammad; Ali, Sher (sourcecoder, 2024)
Within the context of Pakistani Urdu fiction tolerance emerges as a multifaceted concept, encompassing not only religious and ethnic diversity but also socioeconomic disparities and ideological differences. Pakistani Urdu fiction often delves into historical and contemporary events, providing readers with a lens through which to examine the complexities of interfaith relations, communal harmony and the challenges of navigating a pluralistic society. Through their writings readers have been encouraged to cultivate a spirit of tolerance, recognizing that embracing diversity is not only a societal virtue but a pathway to collective growth and wellbeing. This article explore the concept of tolerance in a well-known Pakistani Urdu fiction writer Ishfaq’ Ahmed fiction. Love and tolerance has always been the favorite subject of Ishfaq Ahmed’s writings. Mutual co- existence, harmony٫ multiculturalism and religious and cultural tolerance are the main themes of many of his short stories.